Two new species of the genus Salmoneus Holthuis, 1955 (Dacapoda: Caridea: Alpheidae) from the Western Pacific - Ashrafi, Hossein; Ďuriš, Zdeněk (Zootaxa, 2025)
During two field surveys, one to Papua New Guinea organized by MNHN in 2014, and one to Vietnam in 2007, two specimens of previously undescribed species of the genus Salmoneus Holthuis, 1955, were collected. The first species, S. gimlii sp. nov., is distinguished by its dorsally setose body with short and relatively thick setae, presence of a subminor cheliped, the morphology of its major and subminor chelipeds, and a small rostrum and orbital teeth. The Vietnamese species, S. secundus sp. nov., is characterized by the specific armature of its major and subminor chelipeds. The latter species also exhibits a unique asymmetry in the sixth pleuron, with one side possessing a complete articulated flap and the other an incomplete one. The discovery of these two new species increases the known Salmoneus species count from Papua New Guinea to seven, and from Vietnam to nine.